Scientific models and analysis for enhancing seismic safety of Uzbekistan’s roads and aerodromes - In’omjon Gulomovich Ganiyev; Dilnavo Khamdamova (Science and Education, 2026)
Uzbekistan is located within seismically active zones, which increases the hazard level for highways, bridges, pipelines/culverts, and aerodrome pavements. This paper proposes an integrated system of scientific models aimed at assessing and improving the seismic stability and performance of road and aerodrome infrastructure: (I) probabilistic seismic hazard analysis (PSHA) and spectral intensity parameters; (II) computational models for geotechnical hazards (liquefaction, seismic settlement, and slope instability); (III) evaluation of the dynamic response of pavement structures; (IV) fragility curves and reliability indices for quantifying risk indicators based on damage probability; and (V) life-cycle cost (LCC) and resilience metrics. As a result, a prioritization algorithm for engineering measures to reduce seismic risk is formulated, and preventive strengthening strategies for highway and aerodrome pavements are developed.